2011
DOI: 10.1620/tjem.225.161
|View full text |Cite
|
Sign up to set email alerts
|

Superantigenic Toxin Genes Coexist with Specific Staphylococcal Cassette Chromosome mec Genes in Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is a leading cause of human disease in the hospital setting and the community. Superantigenic toxin-producing methicillin-resistant Staphylococcus aureus (MRSA) is currently important for nosocomial infections and food-borne diseases worldwide because of its global spreading and difficulty in therapy. Superantigenic toxins can bypass normal antigen presentation and have strong T cell mitogenic activity, leading to massive release of proinflammatory cytokines and contributing to the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
11
3
Order By: Relevance
“…The results obtained from this study showed a high resistance of K. pneumonia isolates to cefixime, cefotaxime, ceftriaxone, ceftazidime, and trimethoprim/sulfamethoxazole. This is similar to recent articles in which resistances ranged between 50% and 99% for cefotaxime (3,28) and was up to 20% for trimethoprim-sulfamethoxazole (29). In our hospital, the high resistance of K. pneumonia to cefixime, cefotaxime, ceftriaxone, and ceftazidime was a disturbing finding since these are among the most widely used empirical therapies for febrile infections such as UTI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained from this study showed a high resistance of K. pneumonia isolates to cefixime, cefotaxime, ceftriaxone, ceftazidime, and trimethoprim/sulfamethoxazole. This is similar to recent articles in which resistances ranged between 50% and 99% for cefotaxime (3,28) and was up to 20% for trimethoprim-sulfamethoxazole (29). In our hospital, the high resistance of K. pneumonia to cefixime, cefotaxime, ceftriaxone, and ceftazidime was a disturbing finding since these are among the most widely used empirical therapies for febrile infections such as UTI.…”
Section: Discussionsupporting
confidence: 91%
“…The worldwide development of multidrug resistant (MDR) strains of K. pneumonia is a growing public health issue and is a serious concern for the medical community (2). Extendedspectrum β-lactamase (ESBL)-producing strains of K. pneumonia (ESBLKP) have emerged as a major problem in hospitalized as well as community-based patients (3). In gram-negative bacteria, production of β-lactamases is a major means of resistance to β-lactam antibiotics (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that the carriage characteristic of virulence genes, includ- ing superantigen, adhesion, hemolysin, and leukocidin genes, varied with clone lineage, and the prevalent clone from different geographical origins likewise varied (26)(27)(28). In Japan, the predominant clone is ST5, and seo is the most abundant SAg gene in MRSA isolates (28).…”
Section: Discussionmentioning
confidence: 99%
“…aureus genome harbours many toxin-encoding genes, which are mostly located on mobile genetic elements (MGEs), leading to a pronounced heterogeneity in toxin production among individual S. aureus strains [18]. aureus genome harbours many toxin-encoding genes, which are mostly located on mobile genetic elements (MGEs), leading to a pronounced heterogeneity in toxin production among individual S. aureus strains [18].…”
Section: Staphylococcal Superantigens and Virulence Factorsmentioning
confidence: 99%